Aquatic Center with High-Tech Architecture Approach in South Tangerang City - I'dad Mutawaduil A'la; Diharto; Eko Budi Santoso; Wiwit Setyowati (Universitas Negeri Semarang, 2025)
Aquatic sports are among the disciplines contested in both national and international championships. The design of the Aquatic Center in South Tangerang City aims to serve as a central facility for physical activity and personal development for both aquatic athletes and non-athletes, supporting the improvement of performance and specialized training in swimming, diving, water polo, and artistic diving. This Aquatic Arena provides a training space equipped with internationally standardized facilities, including a 50-meter competition pool, a diving pool, a warm-up pool, and other supporting amenities, making it suitable for hosting competitions at both national and international levels. Located on Jl. Graha Raya Bintaro with a site area of approximately 3.5 hectares, the project also aims to complement the competition facilities of the GBK Aquatic Stadium and contribute to the development of human resources through aquatic sports. As a distinctive architectural identity, the design adopts a High-Tech Architecture approach to realize a wide-span structure that emphasizes the form and façade of the building. The visual character of the facility will be dominated by materials such as metal, aluminum, steel, and glass, ensuring not only an attractive form but also environmental sustainability, safety, and user comfort.